PARENTAL FINANCIAL TEACHING AS A MODERATOR BETWEEN FINANCIAL BEHAVIOR AND SELF-ESTEEM AMONG SUCCESSORS IN FAMILY BUSINESSES - Budi Martono, Sarah Oktania Purnomo; Yosia Wiryakusuma, I Gusti Bagus; Azis Ameyra, Maharani Qhayla Dhyapitaloka (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to examine the financial behavior of family businesses with a focus on the mediating role of self-esteem. This study uses the PLS-SEM research method using survey data collected from 115 respondents. The respondents are family business owners or managers throughout Indonesia. The results showed that financial management in a business influences the financial behavior of family businesses. In addition, Parental Financial Teaching was also found to have a partial mediating effect between family business characteristics and family business financial behavior. These findings suggest that Parental Financial Teaching is an important factor to consider in understanding family business financial behavior. Family business owners with good self-esteem tend to have better financial behaviors, such as being more careful in making financial decisions, more disciplined in financial management, and more open to seeking new opportunities.